Modal analysis of the deep-water solitary scleractinian, Desmophyllum dianthus, on SW Pacific seamounts: inferred recruitment periodicity, growth, and mortality rates - Thresher, R E; Adkins, J; Thiagarajan, N (CORAL REEFS, 2011)
Little is known about the demography of corals inhabiting deep-sea features due to the logistical difficulties of working at the extreme depths they inhabit. To obtain basic information about growth, mortality, and recruitment dynamics for such a coral, we applied modal analysis to the size frequency distributions of live-caught and sub-fossil specimens of the widely distributed solitary cup coral, Desmophyllum dianthus, collected on SW Pacific seamounts. Comparison of live-caught material collected in 1997 and 2007-2009 indicated modal progression over time and an implied maximum age of approximately 190 years, which is similar to ages determined previously for D. dianthus using radiometric techniques. A log-linear decline in the number of individuals with increasing size further implies a constant adult mortality rate, of 15.1{%} per annum in 1997 and 9.2{%} per annum in 2007-2009. The spacing of size modes in the 2007-2009 samples suggests regularly episodic recruitment events, at 22- to 32-year intervals, which may relate to periodic variability in large-scale Southern Ocean circulation. Preliminary analyses of size frequency distributions of the sub-fossil material suggest that the trophodynamics, growth, and adult mortality schedules of D. dianthus in the SW Pacific have remained basically similar throughout the Holocene.
Keywords: AUV ABE (Autonomous Benthic Explorer); ROV Jason (Remotely Operated Vehicle)